Kepemimpinan Visioner dan Manajemen Efektif dalam Meningkatkan Mutu Sekolah (Indo-MathEdu Intellectuals Journal, 2025)
Visionary leadership and effective management play a crucial role in improving educational quality by creating synergy between the leader's strategic vision and organized managerial steps. This study aims to examine the role of school principals in building a long-term vision that is responsive to modern educational challenges and its effective implementation through structured management. Using a qualitative approach with a case study design at SMK Darussalam Blokagung, data were collected through in-depth interviews, observations, and document analysis. The findings reveal that a collaborative work culture driven by visionary leadership can engage all school elements to contribute to shared goals, foster sustainable innovation, and ensure adaptation to technological and curricular changes.